1994
DOI: 10.1001/jama.1994.03520170045034
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Cholesterol and Coronary Heart Disease Mortality and Morbidity and All-Cause Mortality in Persons Older Than 70 Years

Abstract: Our findings do not support the hypothesis that hypercholesterolemia or low HDL-C are important risk factors for all-cause mortality, coronary heart disease mortality, or hospitalization for myocardial infarction or unstable angina in this cohort of persons older than 70 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
139
2
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 397 publications
(156 citation statements)
references
References 22 publications
10
139
2
5
Order By: Relevance
“…A similar pattern of the protective effects of cholesterol has also been found among adults older than 55, who evince an inverse relationship between total cholesterol and several infectious diseases (Iribarren et al 1998). Conversely, studies of younger adults reveal that the effect of total cholesterol on noncardiovascular mortality is neutral (Kronmal et al 1993;Krumholz et al 1994;Gould et al 1995). Another study finds a trend of increased noncardiovascular mortality with decreased LDL, in both placebo and treatment groups (Razzolini et al 2008).…”
Section: Cholesterol and Infectionsupporting
confidence: 54%
“…A similar pattern of the protective effects of cholesterol has also been found among adults older than 55, who evince an inverse relationship between total cholesterol and several infectious diseases (Iribarren et al 1998). Conversely, studies of younger adults reveal that the effect of total cholesterol on noncardiovascular mortality is neutral (Kronmal et al 1993;Krumholz et al 1994;Gould et al 1995). Another study finds a trend of increased noncardiovascular mortality with decreased LDL, in both placebo and treatment groups (Razzolini et al 2008).…”
Section: Cholesterol and Infectionsupporting
confidence: 54%
“…Whereas low HDL-cholesterol is predictive of cardiovascular disease even among people >70 years old [29,30], observational studies in the elderly have either shown no predictive effect of plasma LDL-cholesterol or a protective effect of higher concentrations [3][4][5][6]. In a large population-based cohort of elderly people in the USA, 20% of whom had diabetes, the protective effect of higher concentrations of total choles- terol disappeared after adjustment for markers of poor health, suggesting confounding effects of comorbidity and frailty [5].…”
Section: Discussionmentioning
confidence: 99%
“…This association is weaker in older people, with an apparent paradoxical protective effect of high concentrations of cholesterol in some observational studies [2][3][4][5][6][7]. Measurement of plasma apolipoprotein (Apo) B and ApoA-I improves the prediction of cardiovascular disease, allowing identification of high-risk individuals who are not identified by the standard lipid profile [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The role of RFs on cardiovascular morbidity and mortality may be influenced by age [10], gender [11], and by ethnic or geografic factors [12].…”
Section: Age and Gendermentioning
confidence: 99%